1989
DOI: 10.1055/s-2007-1009257
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the Chlorinating Activity of Human Myeloperoxidase by Thyroid Hormones and Analogues

Abstract: Thyroxine and triiodothyronine concentrations of 50 nM or lower can stimulate the chlorinating activity of the myeloperoxidase-H2O2-Cl- antimicrobial system in vitro. The initial rates of the chlorinating reaction with monochlorodimedone were similar for both thyroid hormones. Maximum stimulation occurred around pH 6 and a linear relationship exists between stimulation and thyroxine concentrations up to at least 1 microM. Of the various thyroxine analogues tested, stimulation was in the order: T4 (or T3) great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…Polymorphonuclear leucocytes from hyperthyroid rats have an enhanced capacity to produce superoxide when stimulated in vitro and this seems primarily related to thyroid-hormoneenhanced NADPH oxidase activity. A similar effect has been observed in phagocytes from hyperthyroid humans (58). Both T4 and T3 can also stimulate, in vitro, the activity of myeloperoxidase isolated from human leukocytes (59).…”
Section: Thyroid Hormones Paradoxsupporting
confidence: 72%
See 1 more Smart Citation
“…Polymorphonuclear leucocytes from hyperthyroid rats have an enhanced capacity to produce superoxide when stimulated in vitro and this seems primarily related to thyroid-hormoneenhanced NADPH oxidase activity. A similar effect has been observed in phagocytes from hyperthyroid humans (58). Both T4 and T3 can also stimulate, in vitro, the activity of myeloperoxidase isolated from human leukocytes (59).…”
Section: Thyroid Hormones Paradoxsupporting
confidence: 72%
“…Other experimental stuy on adult, white, Wistar rat reports a significant increase in lipid peroxidation and proteins carbonyl in the main thyroid hormones target tissues: thyroid gland, heart, liver, skeletal muscle, brain (53,54,55,56). Higher levels of mitochondrial enzymes and increased ROS production by submitochondrial particles has also been reported for hyperthyroid rats (57,58).…”
Section: Thyroid Hormones Paradoxmentioning
confidence: 92%
“…39 However, T4 was found to be ineffective in the absence of Cl Ϫ , thus suggesting that the hormone stimulated HOCl generation. 41,42 It has been reported by Durmuş et al 43 that the elevation in the intraperitoneal concentration of the bacteria caused thyroid hormones to decline in experimentally developed sepsis.…”
Section: Discussionmentioning
confidence: 98%
“…3 Van Zyl et al 41,42 showed that leukocytes concentrated iodine. The preincubation of thyroxine in the myeloperoxidase system showed thyroxine to be oxidized to a product capable of stimulating NADH oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation